Pola Penerapan Implementasi Teknologi Tepat Guna Berbasis Machine Learning dalam Identifikasi Keramik sebagai Infrastruktur Wisata Edukasi di Desa Pagelaran - Abdul Rahman Prasetyo; Iriaji; Ike Ratnawati; Alby Aruna; Eka Putri Surya; Adinda Marcelliantika; Nila Rahmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The application pattern of appropriate technology based on machine learning for ceramic identification as educational tourism infrastructure in Pagelaran Village aims to enhance the effectiveness and efficiency of the ceramic identification process. This program employs machine learning algorithms to classify and recognize various types of ceramics based on visual and textural characteristics. Through this approach, educational tourism in Pagelaran Village can offer an interactive and immersive learning experience for visitors. Initial results indicate increased accuracy in ceramic identification and heightened visitor interest and engagement. This initiative is expected to support the development of technology-based educational tourism in Pagelaran Village.